1998
DOI: 10.1029/97wr03135
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of climate variability on the operational forecast and management of the Upper Des Moines River Basin

Abstract: Abstract. Data from the regulated 14,000 km 2 upper Des Moines River basin and a coupled forecast-control model are used to study the sensitivity of flow forecasts and reservoir management to climatic variability over scales ranging from daily to interdecadal. Robust coupled forecast-control methodologies are employed to minimize reservoir system sensitivity to climate variability and change. Large-scale hydrologic-hydraulic prediction models, models for forecast uncertainty, and models for reservoir control a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 14 publications
1
34
0
1
Order By: Relevance
“…These findings are consistent with those of Georgakakos et al, 1998a. The value of different forecast forms is investigated, demonstrating that forecast uncertainty characterization is important for reservoir management.…”
Section: Introductionsupporting
confidence: 75%
“…These findings are consistent with those of Georgakakos et al, 1998a. The value of different forecast forms is investigated, demonstrating that forecast uncertainty characterization is important for reservoir management.…”
Section: Introductionsupporting
confidence: 75%
“…make their design robust to a wide array of future circumstances, water managers should base their estimates on a range of future scenarios thereby covering the future impacts of inter-annual variability and taking into account possible worst-case conditions (Hall and Borgomeo, 2013;Hallegatte, 2009;Klein, 2003;Wilby and Dessai, 2010). The impact of climate variability on the operational forecast and management of reservoirs was discussed earlier by Georgakakos et al (1998) for a case study in the Upper Des Moines River basin (USA). The same authors showed for a case study in Northern California (Georgakakos et al, 2012) that adaptive, risk based reservoir adaptation strategies, which have the ability to deal with increases in variability under climate change, perform more robustly under future conditions than the traditional rigid operation plans.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…This is an active research area with several past and on-going studies, including Lettenmaier and Rind 1992;Stamm et al 1994;Conway 1998;Wood et al 2004;Georgakakos et al 1998;VanRheenen et al 2004;Tanaka et al 2006;Maurer 2007;Medellín-Azuara et al 2008;Vicuna et al 2009;Georgakakos et al 2011;and Georgakakos et al 2010. Among these studies, general circulation models (GCMs) are broadly used as an important tool for quantitative impact assessment.…”
Section: Introductionmentioning
confidence: 98%